2003
DOI: 10.1261/rna.2116303
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal localization of translation initiation factor IF2

Abstract: Bacterial translation initiation factor IF2 is a GTP-binding protein that catalyzes binding of initiator fMet-tRNA in the ribosomal P site. The topographical localization of IF2 on the ribosomal subunits, a prerequisite for understanding the mechanism of initiation complex formation, has remained elusive. Here, we present a model for the positioning of IF2 in the 70S initiation complex as determined by cleavage of rRNA by the chemical nucleases Cu(II):1,10-orthophenanthroline and Fe(II):EDTA tethered to cystei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
56
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 88 publications
(107 reference statements)
6
56
0
Order By: Relevance
“…In contrast, domain II contacted the body of the small ribosomal subunit. In vitro chemical probing studies using tethered nucleic acid cleavage agents and footprinting techniques to introduce cleavages in the rRNA supported the findings of the cryo-EM studies and revealed IF2 and eIF5B G domain contacts with the large ribosomal subunit and eIF5B domain II contacts with the small subunit (29,31,54). However, it is noteworthy that no genetic data supporting the in vivo relevance of these statically determined binding sites have been reported.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…In contrast, domain II contacted the body of the small ribosomal subunit. In vitro chemical probing studies using tethered nucleic acid cleavage agents and footprinting techniques to introduce cleavages in the rRNA supported the findings of the cryo-EM studies and revealed IF2 and eIF5B G domain contacts with the large ribosomal subunit and eIF5B domain II contacts with the small subunit (29,31,54). However, it is noteworthy that no genetic data supporting the in vivo relevance of these statically determined binding sites have been reported.…”
mentioning
confidence: 64%
“…Derivatization of single cysteine mutants of eIF5B and cleavage reactions were performed essentially as described by Marzi et al (31). The extent of Fe(II)-1-(p-bromoacetamidobenzyl)-EDTA [Fe(II)-BABE] modification for each mutant was examined using the thiolspecific fluorescent reagent 7-diethylamino-3-(4Ј-(iodoacetyl)amino)phenyl)-4-methylcoumarin (DCIA) (Molecular Probes, Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to bacterial (McCutcheon et al 1999;Carter et al 2001;Dallas and Noller 2001;Marzi et al 2003) and eukaryal factors (Lomakin et al 2003;Fraser et al 2007;Unbehaun et al 2007), the localization of archaeal translation initiation factors on the ribosome is unknown. Here, we present the first probing data for S. solfataricus aIF1 on the 30S subunit, provide evidence for a fidelity function of aIF1, and show that this factor in conjunction with aIF1A stimulates binding of a/eIF2 to the 30S ribosomal subunit.…”
Section: Introductionmentioning
confidence: 99%
“…The first major step in the process is assembly of the 30S preinitiation complex. In this complex, fMet-tRNA fMet is paired to the start codon of mRNA in the 30S subunit P site, IF1 occupies the 30S A site, IF2 d GTP binds an adjacent position and interacts specifically with the acceptor end of fMet-tRNA fMet , and IF3 binds the platform of the 30S subunit near the P and E sites (Moazed et al 1995;McCutcheon et al 1999;Carter et al 2001;Dallas and Noller 2001;Marzi et al 2003;Allen et al 2005). The order of assembly remains unclear, and it has been proposed that mRNA and fMet-tRNA fMet associate in random order (Gualerzi et al 2001).…”
Section: Introductionmentioning
confidence: 99%